ANALISIS FAKTOR PENDORONG DAN PENARIK WISATAWAN BERKUNJUNG KE LABUAN BAJO, KABUPATEN MANGGARAI BARAT - Santi Jaimun, Susana; Suardana, I Wayan; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020), 2020)
Labuan Bajo is one of the 10 priority destinations, which   the  Govermment is currenty focusing on in developing both its attraction and facilities that support the sustainability of the tourism activities. To support this goverment policy, Labuan Bajo regional tourism   actors must understand the needs of tourists and develop and maintain existing touris attractions, so that they can attract torists to visit. The purposes of this research are to anlyses the push and pull factors that motivate the tourist traveled to Labuan Bajo. The sampling technique used purposive sampling by distributing 100 questionnaires via google form to tourist who have visited Labuan Bajo. The data was used the likert scale model questionnaire  which was calibated using the coefficient 0,5. The data analysis technique is descriptive quantitative using factor analysis and processed by the application SPSS 23.0 for windows. The data collection technique are interviews, observation, literature and questionnaires. The results showed were four factors that push tourists to visit Labuan Bajo, namely Escape, novelty, prestige, and looking for luxurious and exclusive places and seven  factors that pull tourists to visit Labuan Bajo, namely hunting, culture and history, budget, facilities, ease to travel. , affordable food and beverage prices as well as cleanliness and safety of facilities. The dominant factor that push tourists to visit Labuan Bajo is the escape factor with an eigenvalue 2,029 with a diversity of indicators of 16,912%, while the dominant factor that pull tourists to visit Labuan Bajo is hunting with an eigenvalue of 2,554 and a diversity of indicators of 13,441%.